Refugee - Gratz, Alan (New York : Scholastic Press, 2017)
Although separated by continents and decades, Josef, a Jewish boy living in 1930s Nazi Germany; Isabel, a Cuban girl trying to escape the riots and unrest plaguing her country in 1994; and Mahmoud, a Syrian boy in 2015 whose homeland is torn apart by violence and destruction, embark on harrowing journeys in search of refuge, discovering shocking connections that tie their stories together.
Keywords: Emigration and immigration -- Fiction; Fiction